CEZAC 06”: NEW JASPEADO GARLIC CULTIVAR FOR THE NORTHEM-CENTRAL REGION OF MEXICO - Reveles-Hernández, Manuel; Velásquez-Valle, Rodolfo; Alvarado Nava, María Dolores; Rubio-Díaz, Salvador (Revista Mexicana de Ciencias Agrícolas, 2018)
About 5 200 hectares of garlic are cultivated in Mexico; the north-central region is one of the main producing areas of this vegetable. The lack of locally adapted varieties of garlic is a serious disadvantage for garlic producers. In this paper are mentioned the main agronomic characteristics of “CEZAC 06”, a new garlic variety available for producers of Zacatecas, Aguascalientes, Durango, Chihuahua and Coahuila. The main advantages of this variety are higher yield, consistently round bulbs, fewer numbers of cloves per bulb and homogeneous maturation. In commercial plots, yield has improved in 9-17% and there have been achieved yields of up to 30 t ha-1 using “CEZAC 06”.
Keywords: Allium sativum L.; garlic; Jaspeado; improvement; variety